Mistifikasi Jalinan Komunikasi Pada TVC Air Minum Dalam Kemasan - Irwanto Irwanto; Laurensia Retno Hariatiningsih; Dito Anjasmoro Ningtyas (Jurnal Komunikasi, 2022)
Abstract - This is a study that reveals how mystification is packaged using the narrative of mother-child communication in the Mother's Day version of the Aqua branded beverage product advertisement. The mother's day version of Aqua's advertising communicator takes advantage of the nature of a mother who always loves and protects, especially to her children and the momentum is released to coincide with the events of Mother's Day. This study uses a qualitative approach by using a critical paradigm. then analyze the sign of communication used in advertising by using Barthes semiotics. The unit of analysis is taken purposively and in the form of audio, visual and text. Barthes' idea about the relation between signifier, sign and then the meaning of denotation, connotation and myth led researchers to a finding that advertising communicators perform mystification very subtly. There is a personification of Aqua water as if it has love and protection like a mother The construction process carried out by Aqua advertising communicators is also a myth. Next, he packs the scene of the child's communication relationship with his parents as his denotative aspect and the scene of giving gifts as the connotation of the gimmick he uses. In this study, it was also found that capitalism cannot be separated from the ideology that underlies the communicators of the Mother's Day version of Aqua advertising to do mystification.Keywords : Mystification, Advertising, Capitalist, Construction, Semiotics